Socio-environmental Conflict, Political Settlements, and Mining Governance: A Cross-Border Comparison, El Salvador and Honduras. (March 2019) - Bebbington, Anthony; Fash, Benjamin; Rogan, John
During the mid-2000s, Honduras and El Salvador implemented mining moratoria. By 2017 El Salvador had legislated a globally unprecedented ban on all forms of metal mining, while in Honduras mining was expanding aggressively. These neighboring countries present the explanatory challenge of understanding the distinct trajectories of mining policy and politics. These divergent pathways can be explained by the interactions between the political economy of subsoil resources, national political settlements, and the ways in which diverse actors have taken advantage (or not) of openings in these settlements. A mediados de la década del 2000, Honduras y El Salvador implementaron moratorias mineras. Para el 2017, El Salvador había legislado una prohibición sin precedentes a nivel mundial de todas las formas de minería de metales, mientras que en Honduras la minería se estaba expandiendo agresivamente. Estos países vecinos presentan el desafío explicativo de comprender las distintas trayectorias de la política minera y la política. Estas vías divergentes pueden explicarse por las interacciones entre la economía política de los recursos del subsuelo, los acuerdos políticos nacionales y las formas en que diversos actores han aprovechado (o no) las aperturas en estos acuerdos.